The prevention of hospital-acquired pressure injuries among adult immobilized patients in a mental health department: a best practice implementation project. Issue 1 (14th March 2023) - Dobre, Claudia E.; Gagiu, Corina; Jitianu, Dorinela A.; Zazu, Mariana; Mazilu, Doina C.; Jiménez, Marina Gallego
ABSTRACT: Objectives: The aim of this implementation project was to promote evidence-based practices regarding hospital-acquired pressure injuries prevention practices among immobilized adult patients in a mental health department and to measure the level of compliance with the best practice in this field. Introduction: Pressure injuries can have significant restrictions on the patient's quality of life; affect the patient physically, psychologically, and socially; lead to increased costs and length of hospital stay; and are closely linked to increased mortality. Thus, the best evidence practice implementation project was conducted in the mental health ward of a large teaching hospital in Bucharest. Method: The current evidence implementation project used the JBI Practical Application of Clinical Evidence System and Getting Research into Practice. The best practices project was carried out in a mental health department with 70 beds at Bucharest's largest mental health hospital. This analysis of nursing practice included all immobile patients who were hospitalized in the ward. Results: Through the project to implement best practices for the prevention of pressure injuries, the activity of nurses was improved. If initially, the prevention of pressure injuries was a deficient activity in the hospital (compliance between 0 and 82%), after the implementation of the project, compliance with the recommendations of evidence-based practices was radically improved, obtaining a maximum percentage of 100% for all these activities: patient assessment, use of assessment tools, use of necessary devices, provision of high protein diet and patient education. Conclusion: The current project contributed to the standardization and improvement of nurses' practice of pressure injuries prevention in patients with mental illness and immobility hospitalized in a psychiatric ward. The development of future audits will help identify the sustainability of the implemented prevention measures.